The Impact Of A Training Program For The Injury Of The Connective Muscle In The Improvement Of Some Of The Capabilities Of Compatibility (the Ability To Balance) .field Study Of Some Clubs In The State Of Bordj Bou Arreridj U15 - Saadsaoud Foued; Taoui Saddam Houcin . (sports creativity, 2025)
The most common muscle injury in the athlete is the pubalgia, which affects the adductor muscle, which is located inside the thigh. It is called the adductor muscle because it brings the thigh back inside.The adductor muscle is damaged by pressure on the muscle nerve, causing weakness and inflammation of the sac of the femoral muscle resulting from repeated muscle irritation during exercise, and bad warm-up. all this inflicts on players' performance and exposes them to injury. The aim of the study is to find a group of low-intensity exercises as part of a qualifying sports program.The researcher focused on the proposed rehabilitation program to improve the player's compatibility abilities. of football. The community of the study is in Bordj Bou Arreridj, CABBA, star of Bordj, football clubs in Bordj Bou Arreridj U15 Keywords: Connective muscle. Harmonic capacity. Rehabilitation program